2010
DOI: 10.1002/adfm.200901775
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Ribbed Nanoneedles with Robust Superhydrophobicity

Abstract: The robustness of superhydrophobicity is a fundamental issue for the applications of water‐repellent materials. Inspired by the hierarchical structures of water‐strider legs, this work describes a new water‐repellent material decorated with ribbed, conical nanoneedles, successfully achieved on the surface of copper and consisting of copper hydroxide nanoneedle arrays sculptured with nanogrooves. The behavior of water drops on an as‐prepared surface under various external disturbances is investigated. It is sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
154
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(157 citation statements)
references
References 29 publications
2
154
1
Order By: Relevance
“…Accordingly, the nonaligned structures may also be used to create more efficient condensation heat-transfer surfaces as long as the surface adhesion of each nanoneedle is sufficiently low to ensure the efficient self-removal of suspended condensate microdrops via mutual coalescence. Inspired by the conical setae of the legs of the water strider, Yao et al [101] developed a type of clustered copper hydroxide ribbed-nanoneedle structure with robust superhydrophobicity. During the squeezing and relaxation process of the tested water droplets, the surface adhesion of functional films and nanoneedle sidewalls is negligibly low, which may be ascribed to the synergetic effect of the sharp tip and hierarchical surface nanogrooves of the nanoneedles.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Accordingly, the nonaligned structures may also be used to create more efficient condensation heat-transfer surfaces as long as the surface adhesion of each nanoneedle is sufficiently low to ensure the efficient self-removal of suspended condensate microdrops via mutual coalescence. Inspired by the conical setae of the legs of the water strider, Yao et al [101] developed a type of clustered copper hydroxide ribbed-nanoneedle structure with robust superhydrophobicity. During the squeezing and relaxation process of the tested water droplets, the surface adhesion of functional films and nanoneedle sidewalls is negligibly low, which may be ascribed to the synergetic effect of the sharp tip and hierarchical surface nanogrooves of the nanoneedles.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The chemical baths used for coating contained 1.0 % of octadecyltrimethoxysilane (ODTMS, from Fisher Scientific) [35], 1.0 % of heptadecafluorodecyltrimethoxysilane (FAS, from Shin Etsu Chemical Co.) [36], or 5.0 mM stearic acid (SA, from Wako) [37].…”
mentioning
confidence: 99%
“…The solvents were ethanol/water (9:1 v/v) [35], methanol/water (9:1 v/v) [36], and pure ethanol [37], respectively. All the coating protocols applied in this study are widely used by others and their description can be found in greater detail elsewhere [35][36][37].…”
mentioning
confidence: 99%
“…1D) [18,19]. The legs of water striders are covered with numerous needleshaped setae arranged in a similar orientations at the micron scale, with a tilt angle of approximately 20 • from the surface [20].…”
Section: Insectsmentioning
confidence: 99%
“…The legs of water striders are covered with numerous needleshaped setae arranged in a similar orientations at the micron scale, with a tilt angle of approximately 20 • from the surface [20]. Inspired by the water strider legs, some multiscale structured materials with a superhydrophobic surface have been developed [18,21]. Zhang et al prepared superhydrophobic coatings on a gold thread to compare their forces and motions on gold wires supported on water surfaces (Fig.…”
Section: Insectsmentioning
confidence: 99%